ADAPTATION AND SYSTEMATIZATION OF TEACHING MATERIALS FOR INDIVIDUALS AND GROUPS - Ataboyev, Isroil; Rustamov Ilkhom Tursunovich, Rustamov Ilkhom Tursunovich (Журнал иностранных языков и лингвистики, 2023)
Our article is devoted to the principles on which modern teaching materials and teaching methods are built. It also aims to systematize the structure of events and classes and standard practical materials for self-management and problems. When adapting educational materials to a specific learning environment, attention should be paid to factors that are taken into account, where there is a need to change and manipulate certain design features. There is a direct relationship between the evaluation and adaptation of materials from the point of view of the reasons for this and the criteria used. Adaptation is a process of adaptation.